Modeling and parametric analysis of an adsorber unit for thermal energy storage. (1st May 2016) - Fernandes, M.S.; Brites, G.J.V.N.; Costa, J.J.; Gaspar, A.R.; Costa, V.A.F.
Abstract: The dynamic model of an adsorber unit used as thermal energy storage device immersed in water is presented. The system operates with the silica-gel/water pair and is capable of storing the thermal energy received from the surrounding water ( e . g ., excess heat input from a hot water storage tank), in order to give it back later to the water as adsorption heat. The model was developed following a lumped parameter approach implemented in MATLAB ® code. The performance of the absorber unit was assessed by a set of parametric tests under different geometric configurations and temperature conditions. The mass of adsorbent was found to have a higher impact on the thermal energy exchange than the surface contact area between metal and adsorbent. An improved finned adsorber, with 27 internal longitudinal fins and 120 external annular fins, resulted in a heat output to the water 2.3 times higher than with a similar finless adsorber. Moreover, the evaporation temperature effect was found to be much higher than the condensation temperature effect. This device seems to be an attractive solution to include, for instance, in solar hot water systems in order to fulfill the thermal energy needs during periods of low solar radiation. Highlights: A dynamic model of a heat storage adsorber unit immersed in water is proposed. The unit can harness the water excess heat in some periods and give it back later. Designed to operate as a heat source supplement in heat storage systems. Adsorbent mass and evaporation temperature strongly affect the unit's performance. An improved finned adsorber provides a 2.3 higher heat output than a finless version.